Thermal performance of two heat exchangers for thermoelectric generators. (September 2016) - Li, W.; Paul, M.C.; Siviter, J.; Montecucco, A; Knox, A.R.; Sweet, T.; Min, G.; Baig, H.; Mallick, T.K.; Han, G.; Gregory, D.H.; Azough, F.; et al.
Abstract: The thermal performance of a heat exchanger is important for the potential application in an integrated solar cell/module and thermoelectric generator (TEG) system. Usually, the thermal performance of a heat exchanger for TEGs is analysed by using 1D heat conduction theory which ignores the detailed phenomena associated with thermo-hydraulics. In this paper, thermal and momentum transports in two different heat exchangers are simulated by means of a steady-state, 3D turbulent flow k - ε model with a heat conduction module under various flow rates. In order to simulate the actual working conditions of the heat exchangers, a hot block with an electric heater is included in the model. The TEG module is simplified by using a 1D heat conduction theory, so its thermal performance is equivalent to a real TEG. Natural convection effects on the outside surfaces of the computational domains are considered. Computational models and methods used are validated under transient thermal and electrical experimental conditions of a TEG. The two heat exchangers designed in this paper have better thermal performance than an existing heat exchanger for TEGs. More importantly, the fin heat exchanger is more compact and efficient than the tube heat exchanger.